Ab Initio Downfolding Based on the GW Approximation for Infinite-Layer Nickelates - Hirayama, Motoaki; Nomura, Yusuke; Arita, Ryotaro (Frontiers in Physics, 2022)
We derive an effective three-orbital model for the infinite-layer nickelates based on the band structure obtained by the GW approximation (GWA), where we consider the Ni 3$d_{x^2-y^2}$ and O 2$p$ orbitals forming the $¥sigma$-bond. In the GWA, the self-energy correction to the local density approximation (LDA) increases the energy difference between Ni $3d_{x^2-y^2}$ and O $2p$, which reduces the bandwidth of the antibonding 3$d_{x^2-y^2}$ orbitals. The isolation of the Ni $3d_{x^2-y^2}$ around the Fermi level suppresses the screening effect. As a result, the correlation effect becomes more significant than that in the model constructed by the LDA-based downfolding. Furthermore, the Mott-Hubbard type character is enhanced in the GWA-based effective model, because the charge-transfer energy increases more rapidly compared to the increase in the interaction parameters.